Pengembangan Sistem Komunikasi Antar Stakeholder Sekolah Menggunakan Sistem ComGate - Raden Arief Setyawan; Hadi Suyono; Muhammad Fauzan Edy Purnomo (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2017)
Based on the results of communication with the head of PAUD IT Putera Zaman and SMPN-2 Sumberpucung Malang, as well as field surveys were conducted, some of the problems that can be identified are as follows: 1) the deficiency of intensive communication between school with the student’s parent; 2) the deficiency of intensive communication between School with stakeholders, such as donatours. The efective communication should be made based on IT (Information Technology) i.e. via SMS Gateway implementation, so intertwined intensive communication between stakeholders interest in PAUD IT Putera Zaman and SMPN-2 Sumberpucung. The implementation of SMS Gateway has been done by identifying the system requirement and data collection of PAUD IT Putera Zaman’s and SMPN-2 Sumberpucung’s stakeholder. SMS Gateway has been designed and implemented using a combination of Kalkun Application System as contact management and SMS, and Gammu SMS Daemon used as processing of the SMS program such as receiving, storing, and transmitting the messages through GSM modem. The database used is managed by using MySQL to store the existing messages. SMS Gateway with the existing system has been successfully implemented in the PAUD IT Putera Zaman and SMPN-2 Sumberpucung Malang. Result of performance test shows that this sistem could send the message up to 72 message per minute, and received up to 70 message per minutes.